FAKTOR-FAKTOR YANG MEMPENGHARUI KUNJUNGAN IBU HAMIL PADA TRIMESTER PERTAMA DI PUSKESMAS KAIRATU KABUPATEN SERAM BAGIAN BARAT TAHUN 2013 - Yonce Heumasse (Dian Nuswantoro Semarang, 2019)
ABSTRAK Antenatal health services by pregnant women in the first trimester can make it difficult for health workers to provide comprehensive and comprehensive guidance and maintenance for the health of pregnant women, including early detection of risk factors. This is one of the results of the Maternal Mortality Rate in Indonesia (Peranginangin,2010). The purpose of this study was to obtain information about the factors that influence the visit of pregnant women in the first trimester. The research method used in this research is analytic survey research by studying